Hormonal profile in relation to early pregnancy diagnosis and litter size in crossbred sows - BEDI, B R; PANDIT, R K; JOGI, S; SRIVASTAVA, O P; AGARWAL, R G; AGARWAL, R G (The Indian Journal of Animal Reproduction, 2023)
Twelve crossbred sows(½ Large White Yorkshire x ½ Indigenous) were used to diagnose pregnancy and assess their litter size at the earliest through ELISA assayed hormonal profile. The mean concentration of estrone sulfate was 60.17 ± 0.48 ng I ml of serum on the day of service in the sows. It rose to 100.00 ± 0.52 ng / ml on 14th day after service and remained almost same on the 16th day also. Thereafter, it increased to 300.08 ± 0.71 on 18th, 400.08 ± 0.52 on 20th, 702.92 ± 0.07 on 22nd, 1200.08 ± 0.58 on 24th and 1900.08 ± 0.54 ng / ml serum on 26th day of pregnancy. The correlation between serum estrqne sulfate concentration and litter size was significantly positive (P < 0.05) on 22nd ( 0.632) and 24th ( 0.594) days of pregnancy. The mean concentration of the progesterone on the day of service was 9.72 ± 0.75 ng/ ml serum. It rose significantly (P < 0.01) to 25.67 ± 0.44 ng I ml serum on 14th day of pregnancy. Thereafter, upto 26 days of pregnancy the hormonal profile did not vary significantly. The levels of serum estrone sulfate and progesterone concentrations were directly related to pregnancy and litter size.